Understanding the self-initiated expatriate: A review and directions for future research - Doherty, Noeleen (Blackwell Publishing, 2013)
The study of self-initiated expatriates (SIEs) has gained pace in the last decade, focusing on these individuals, their motivations, their behaviours and their relevance to the global workforce. Published works produced between 1996 and 2011 are reviewed. A thematic analysis indicates that key topics of focus in current research cover: characteristics of the self-initiated and their work-related experiences and management; comparative studies of company-backed versus self-initiated expatriation and the self-initiated as global talent flow. This paper identifies a need for clarification of the construct of SIEs, expands on the theoretical perspectives used to examine SIEs and offers a framework to facilitate coherence in the direction of future research and the application of knowledge to practice in this field of study.